2014
DOI: 10.1111/1471-0528.12999
|View full text |Cite
|
Sign up to set email alerts
|

The increase of sexually transmitted infections calls for simultaneous preventive intervention for more effectively containing HIV epidemics in China

Abstract: Objective To identify the priority public health challenges with respect to the development of multipurpose prevention technologies in China. Design Review of published literature, databases of state and local disease control agencies and unpublished data relating to HIV and other sexually transmitted infections (STIs). Setting China. Population General and migrant populations. Methods Review of published data, government reports and databases of China Disease Control agencies, and our unpublished studies. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(69 reference statements)
2
17
3
Order By: Relevance
“…More importantly, this study revealed that age, number of sexual partners, HIV testing, considering oneself as high risk individual to HIV, considering physical contact as route of transmission, poverty, and having only books and newspapers as main source of HIV/AIDS information were factors that increased discrimination of people infected with HIV by medical students; however, deeper knowledge subsequently increases medical students' support towards people living with HIV/AIDS and STIs. In accordance with previous studies [ 8 , 15 , 17 , 31 ], an overlap misconception, confusion, and fears may lead medical students to discriminate and provide poor medical care towards people infected with HIV and STIs infected individuals. Overall, this study provided substantial evidence of reinforcing education of medical students on HIV/AIDS and STIs with a particular interest in foreign students who are limited in HIV/AIDS information.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…More importantly, this study revealed that age, number of sexual partners, HIV testing, considering oneself as high risk individual to HIV, considering physical contact as route of transmission, poverty, and having only books and newspapers as main source of HIV/AIDS information were factors that increased discrimination of people infected with HIV by medical students; however, deeper knowledge subsequently increases medical students' support towards people living with HIV/AIDS and STIs. In accordance with previous studies [ 8 , 15 , 17 , 31 ], an overlap misconception, confusion, and fears may lead medical students to discriminate and provide poor medical care towards people infected with HIV and STIs infected individuals. Overall, this study provided substantial evidence of reinforcing education of medical students on HIV/AIDS and STIs with a particular interest in foreign students who are limited in HIV/AIDS information.…”
Section: Discussionsupporting
confidence: 79%
“…Of note, HIV transmission is mainly drawn by MSM in China [ 5 ]. However, recent studies reported that HIV transmission is shifting into heterosexual populations [ 2 , 8 , 10 , 25 ]. Foreign students were more likely to have more than one sexual partner with inconsistent condom use certainly because they feel uncomfortable with condoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the prevalence of syphilis in China has risen since the 1990s, to prevent syphilis transmission from mother to child has become a priority 10 16. In this study, the overall prevalence of maternal syphilis was much higher than in other parts of the world, such as Europe (0.16%), the Mediterranean (0.06%) and slightly higher than the Chinese national average (0.24%) 1 9.…”
Section: Discussionmentioning
confidence: 60%
“…The annual worldwide incidence of syphilis has increased from 8.4% in 2009 to 11.2% in 2014 (1). The infection and incidence rates of syphilis in China also demonstrated a linear upward trend, and ranked third among all infectious diseases, after viral hepatitis and pulmonary tuberculosis (2,3). Treponema pallidum (Tp), the pathogen of syphilis, has a strong invasive ability and enters the human body through intact mucosa or damaged skin at an early stage of the infection.…”
Section: Introductionmentioning
confidence: 99%